2009
DOI: 10.1108/02635570910939371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of management support, training, and user involvement on system usage and satisfaction in Kuwait

Abstract: Purpose -The purpose of this paper is to investigate the organizational factors and human motivations affecting information systems and information technology (IS/IT) usage and user's satisfaction in an Arabic country. Design/methodology/approach -The study develops a research model that links three organizational factors (top management support -TMS, availability of training, and user's involvement) to IS/IT usage and end-user's satisfaction via the mediation of TAM beliefs (usefulness and ease-of-use) by 382… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 49 publications
2
38
1
7
Order By: Relevance
“…Providing appropriate training and the availability of persons to deal with technical problems enable users to overcome the barriers of using IS/ IT when they face difficulties, resulting in the facilitation of IS utilization [33,35]. Previous studies have suggested that facilitating conditions will increase employees' perceptions of system ease of use [36][37][38][39][40]. As such, we hypothesize that:…”
Section: Facilitating Conditionsmentioning
confidence: 92%
“…Providing appropriate training and the availability of persons to deal with technical problems enable users to overcome the barriers of using IS/ IT when they face difficulties, resulting in the facilitation of IS utilization [33,35]. Previous studies have suggested that facilitating conditions will increase employees' perceptions of system ease of use [36][37][38][39][40]. As such, we hypothesize that:…”
Section: Facilitating Conditionsmentioning
confidence: 92%
“…Several studies have indicated that facilitating conditions are positively associated with perceived ease of use and perceived usefulness (Karaali, Gumussoy, & Calisir, 2011;Rouibah, Hamdy, & Al-Enezi, 2009). In addition, social influence refers to the influence of others on users.…”
Section: Innovations In Education and Teachingmentioning
confidence: 98%
“…Researchers agree upon the definition of user involvement as a subjective psychological state that highly involved persons may have greater personal relevance, affect cognitions, attitudes and behaviours than lowly involved ones (Barki and Hartwick 1989, 1994, Amoako-Gyampah 2007, Rouibah et al 2009). In social and consumer psychology, the role of use involvement has been studied extensively (Sherif and Cantril 1947, Krugman 1965, Petty et al 1983.…”
Section: User Involvementmentioning
confidence: 99%
“…After reviewing conceptualisations of involvement found in other disciplines, such as psychology, marketing and organisational behaviour, researchers separate the concepts of user participation (behaviours or activities joined by users in the system development process) and user involvement (a subjective psychological state indicating the importance and personal relevance of a system to the user; Barki and Hartwick 1989) and then developed separate measures of user participation, user involvement and user attitude (Barki and Hartwick 1994). Rouibah et al (2009) investigated the organisational factors and human motivations affecting information systems and information technology (IS/IT) usage by collecting 382 respondents from public organisations who have had high experience with IS/ IT. Rouibah et al (2009) investigated the organisational factors and human motivations affecting information systems and information technology (IS/IT) usage by collecting 382 respondents from public organisations who have had high experience with IS/ IT.…”
Section: User Involvementmentioning
confidence: 99%